Comparison of Centering Ability and Canal Transportation of TruNatomy Files with Different File Systems - Hazar, Ecehan; Geduk, Gediz; Coşkun, Ezgi; Koçak, Sibel; Sağlam, Baran Can; Koçak, Mustafa Murat (Journal of Dentistry Indonesia, 2023)
Objective: This study aims to evaluate the centering ability and canal transportation of the ProTaper Next, One Curve, and TruNatomy instruments in curved root canals. Methods: Forty-five curved mesiobuccal canals of human mandibular molar teeth were selected, randomly divided into 3 groups, and prepared using the ProTaper Next, One Curve, and TruNatomy files. Cone Beam Computed Tomography images of the cross-sectional planes at 1 mm, 3 mm, 5 mm, and 7 mm from the apical foramen were determined before and after the preparation. For each specified millimeter canal transportation and centering ability were measured. Statistical analysis was performed and compared all groups. Results: No significant differences were observed between the groups or root canal levels in both canal transportation and centering ability (p > 0.05). Conclusion: The TruNatomy system demonstrated comparable results with both predecessor ProTaper Next and One Curve single-file systems.